THE IMPACT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL EFFECTIVENESS CONSIDERING THE MEDIATING ROLE OF INFORMATION TECHNOLOGY - Oday Hussein Ali; Hussein Naser Sharhan; Rafid Khudhur Radhi Alsaedi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Innovation and creativity have become the buzzwords of the HR management discourse in the past twenty years. This is because, they positively contribute to the competitiveness, effective functioning and long-term survival of the organization. Holding the non-linear, intangible and causally ambiguous nature of all the innovative aspects and related phenomena, research and management scholars are eagerly trying to understand the factors, which contribute to innovation and creativity from several lenses starting from employee attitude, organizational behavior right at the micro-level businesses to strategic management issues of the macro-level. Together with them, there are insightful and crucial developments in such research streams, which included HRM research independently from each other, particularly from their strategic program perspective. Indeed, these changes have been implemented recently and they contributed to an informed view and better understanding of the HR mediating role for effectiveness, creativity and innovations. However, that should remain as the major goal of HRM practices, and they should review the strategies and mediation HRM research contribution to improving the understanding of the individual-level creativity and innovation at the entire organization. Taking the innovation funnel as a symbol to review research methods of HRM systems and practices, which assuredly contribute to the creativity of employees and organizational innovation.